2022
DOI: 10.1590/s1677-5538.ibju.2021.0653
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of incidental prostate cancer in certain surgeries for benign prostatic hyperplasia: A systematic review and meta-analysis

Abstract: Background: This study aimed to explore the prevalence and clinical risk factors in patients diagnosed with incidental prostate cancer (IPC) during certain surgeries (transurethral resection of the prostate [TURP], open prostatectomy [OP], and holmium laser enucleation of the prostate [HoLEP]) after clinically suspected benign prostatic hyperplasia (BPH).Materials and Methods: Literature search of the MEDILINE, Web of Science, Embase, and Cochrane Library databases was performed to identify eligible studies pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
1
8
0
1
Order By: Relevance
“…50 Likewise, nonlethal prostate neoplasms can be incidentally encountered in surgeries for benign prostatic hyperplasia (BPH) and cystoprostatectomy (CP) for bladder cancer. [51][52][53][54] Even at autopsy, latent GG 1 prostate cancers are extremely common. 55,56 These inconsequential nonlethal prostate neoplasms inflate the prevalence of prostate cancer, which is currently the leading cancer diagnosis in men, yet only about 3% actually die of the disease.…”
Section: Patients Come Firstmentioning
confidence: 99%
See 2 more Smart Citations
“…50 Likewise, nonlethal prostate neoplasms can be incidentally encountered in surgeries for benign prostatic hyperplasia (BPH) and cystoprostatectomy (CP) for bladder cancer. [51][52][53][54] Even at autopsy, latent GG 1 prostate cancers are extremely common. 55,56 These inconsequential nonlethal prostate neoplasms inflate the prevalence of prostate cancer, which is currently the leading cancer diagnosis in men, yet only about 3% actually die of the disease.…”
Section: Patients Come Firstmentioning
confidence: 99%
“…Most prostate biopsies are performed for elevated PSA and because it is not specific for cancer, a rise due to inflammation or other causes may lead to the sampling of nonlethal microfocal tumors resulting in the unfortunate new label of a “prostate cancer patient” 50 . Likewise, nonlethal prostate neoplasms can be incidentally encountered in surgeries for benign prostatic hyperplasia (BPH) and cystoprostatectomy (CP) for bladder cancer 51–54 . Even at autopsy, latent GG 1 prostate cancers are extremely common 55,56 …”
Section: Motivations For a Nomenclature Changementioning
confidence: 99%
See 1 more Smart Citation
“…Autopsy samples have revealed that approximately 40% of men over 60 years old and nearly 60% of men over 80 years old have prostate cancer. 1,2 Although prostate-specific antigen (PSA) testing has greatly improved the diagnosis and treatment of prostate cancer, reducing the incidence of iPCa by about 65%, it is important to inform patients about the possibility of this diagnosis after surgical interventions for BPH. 1 A review conducted by Yilmaz et al demonstrated a rate of iPCa ranging from 5.64% to 23.3% after holmium laser enucleation of the prostate (HoLEP).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Although prostate-specific antigen (PSA) testing has greatly improved the diagnosis and treatment of prostate cancer, reducing the incidence of iPCa by about 65%, it is important to inform patients about the possibility of this diagnosis after surgical interventions for BPH. 1 A review conducted by Yilmaz et al demonstrated a rate of iPCa ranging from 5.64% to 23.3% after holmium laser enucleation of the prostate (HoLEP). 3 A temporal analysis noted that older patients have an increased incidence of grade group (GG) 1 iPCa that was associated with decrease in rate of preoperative prostate biopsy.…”
Section: Introductionmentioning
confidence: 99%